1996
DOI: 10.1074/jbc.271.25.14712
|View full text |Cite
|
Sign up to set email alerts
|

The Multidrug Resistance-associated Protein (MRP) Subfamily (Yrs1/Yor1) of Is Important for the Tolerance to a Broad Range of Organic Anions

Abstract: We have cloned and characterized a Saccharomyces cerevisiae gene YRS1 that complements the phenotype of the mutant sensitive to the anionic drug reveromycin A. The YRS1 gene, which is identical to the recently identified YOR1 gene, encodes a protein with extensive homology to the human multidrug resistance-associated protein (MRP) and the yeast cadmium factor (Ycf1). A chromosomal deletion of YRS1 lead to viable Deltayrs1 cells, which exhibited hypersensitivity to reveromycin A. Elevation of the YRS1 gene dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 26 publications
(22 reference statements)
0
92
0
2
Order By: Relevance
“…40 -42), the yeast cadmium factor protein (Ycf1p; Refs. 14 -16, 43, and 44) and possibly the yeast Yor1p protein (45). Through the concerted actions of GSTs and the GS-X pumps, cells can confer a common structural determinant on toxins, increase their water solubility, and then eliminate them from the cytosol (1,46).…”
Section: Discussionmentioning
confidence: 99%
“…40 -42), the yeast cadmium factor protein (Ycf1p; Refs. 14 -16, 43, and 44) and possibly the yeast Yor1p protein (45). Through the concerted actions of GSTs and the GS-X pumps, cells can confer a common structural determinant on toxins, increase their water solubility, and then eliminate them from the cytosol (1,46).…”
Section: Discussionmentioning
confidence: 99%
“…The name Yor1p (for yeast oligomycin resistance) reflects that fact that the YOR1 gene was discovered based on its ability to confer resistance to the mitochondrial poison oligomycin when overexpressed and to confer sensitivity when deleted (76). Early on, Yor1p overexpression was also shown to confer resistance to the anionic antifungal drug reveromycin A and the anionic fluorescent compound rhodamine B, leading to the suggestion that Yor1p was a multispecific organic anion transporter (23). However, a large-scale study of several hundred compounds identified many more Yor1p substrates and indicated that Yor1p could transport an impressive variety of compounds with quite distinct chemical features (85,134).…”
Section: Yor1p a Short Abcc At The Plasma Membrane That Mediates Plementioning
confidence: 99%
“…As (III) is exported by the Acr3 transporter (Ghosh et al, 1999;Wysocki et al, 1997). It has been proposed that Yor1 mediates Cd (II) efflux in the form of Cd (GS) 2 (Cui et al, 1996;Nagy et al, 2006). Cd (II) and As (III) GSH-conjugates are imported into vacuole by Ycf1.…”
Section: Cadmium and Arsenate Toxicity The Role Of Oxidative Stressmentioning
confidence: 99%